A Massive Ewing Sarcoma of the Rib: A Case Report with Literature Review. (14th May 2022) - Fahad, Naseem; Hamideh, Dima; Zareef, Rana; Akel, Samir
Abstract : A 9-year-old boy with a 16 cm chest wall mass, presenting with progressive cough and exertional dyspnea, was finally diagnosed with Ewing sarcoma of the rib. Such massive tumors usually present with metastasis and carry a bad prognosis. Fortunately, we present here a successful treatment approach for Ewing sarcoma of the ribs, defeating the overwhelming obstacles commonly faced in chest wall tumors. Delays in diagnosis, misdiagnosis, difficulty with general anesthesia, opportunistic infections, disruptions in chemotherapy delivery, and debilitating chest wall deformities are all potential challenges that could complicate the course of treatment.